The three‐dimensional structure of TrmB, a transcriptional regulator of dual function in the hyperthermophilic archaeon Pyrococcus furiosus in complex with sucrose. (8th May 2013) - Krug, Michael; Lee, Sung‐Jae; Boos, Winfried; Diederichs, Kay; Welte, Wolfram
Abstract: TrmB is a repressor that binds maltose, maltotriose, and sucrose, as well as other α‐glucosides. It recognizes two different operator sequences controlling the TM (Trehalose/Maltose) and the MD (Maltodextrin) operon encoding the respective ABC transporters and sugar‐degrading enzymes. Binding of maltose to TrmB abrogates repression of the TM operon but maintains the repression of the MD operon. On the other hand, binding of sucrose abrogates repression of the MD operon but maintains repression of the TM operon. The three‐dimensional structure of TrmB in complex with sucrose was solved and refined to a resolution of 3.0 Å. The structure shows the N‐terminal DNA binding domain containing a winged‐helix‐turn‐helix (wHTH) domain followed by an amphipathic helix with a coiled‐coil motif. The latter promotes dimerization and places the symmetry mates of the putative recognition helix in the wHTH motif about 30 Å apart suggesting a canonical binding to two successive major grooves of duplex palindromic DNA. This suggests that the structure resembles the conformation of TrmB recognizing the pseudopalindromic TM promoter but not the conformation recognizing the nonpalindromic MD promoter. Abstract : Interactive Figure | PDB Code(s):3QPH